2003
DOI: 10.1128/aem.69.7.3809-3818.2003
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and Adaptive Response to Bile Salts in Propionibacterium freudenreichii : Physiological and Proteomic Analysis

Abstract: Tolerance to digestive stresses is one of the main factors limiting the use of microorganisms as live probiotic agents. Susceptibility to bile salts and tolerance acquisition in the probiotic strain Propionibacterium freudenreichii SI41 were characterized. We showed that pretreatment with a moderate concentration of bile salts (0.2 g/liter) greatly increased its survival during a subsequent lethal challenge (1.0 g/liter, 60 s). Bile salts challenge led to drastic morphological changes, consistent with intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
152
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(164 citation statements)
references
References 47 publications
11
152
0
1
Order By: Relevance
“…Induction of dnaK at the transcriptional level was shown in Bifidobacterium adolescentis following heat, salt, and bile treatments (49). DnaK was induced in Propionibacterium freudenreichii, a microorganism closely related to bifidobacteria, as a response to bile, acid, and heat (32,33) and in B. breve as a response to osmotic shock (58). GroEL clearly responds to acid stress in P. freudenreichii (33) and Streptococcus oralis (61).…”
Section: Resultsmentioning
confidence: 99%
“…Induction of dnaK at the transcriptional level was shown in Bifidobacterium adolescentis following heat, salt, and bile treatments (49). DnaK was induced in Propionibacterium freudenreichii, a microorganism closely related to bifidobacteria, as a response to bile, acid, and heat (32,33) and in B. breve as a response to osmotic shock (58). GroEL clearly responds to acid stress in P. freudenreichii (33) and Streptococcus oralis (61).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, acid pretreatment sensitized cells to bile salts challenge and vice versa. Heat and acid responses did not present significant cross-protection and no cross-protection of salt-adapted cells against heat stress was observed for these propionibacteria [48][49][50].…”
Section: Long Term and Stress Survival Of Propionibacteriamentioning
confidence: 99%
“…Many studies have demonstrated by in vitro assays the ability of dairy propionibacteria to survive and tolerate the gastrointestinal conditions [130][131][132][133][134]. This tolerance could be improved by a pre-adaptation of the microorganisms to the adverse conditions of the gut by a brief exposure to the stressful conditions at a non-lethal level [48,135].…”
Section: Safety and Persistence In The Gutmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells were examined and photographed with S-2700 Scanning Electron Microscope (HITACHI) operating at 20 kV. Micrographs were taken at various magnifications (Leverrier et al, 2003).…”
Section: Drying Processmentioning
confidence: 99%